Manajemen Retribusi Pasar Inpres Desa Bangkir Kecamatan Dampal Selatan Kabupaten Toli-Toli - Amalia, Ika Rezky; Susanti, Ani; Royfandi, Moh. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aims to examine the management of market retribution in Bangkir Village, Dampal Selatan Subdistrict, Toli-Toli Regency. The research adopts a qualitative approach with a descriptive type of study. Data were collected through observation, interviews, and documentation. Both primary and secondary data sources were utilized. Informants were selected using a purposive sampling technique, involving nine individuals considered to have adequate knowledge and understanding of the issues being investigated. The theoretical framework is based on George R. Terry’s management theory, which emphasizes four key aspects: planning, organizing, actuating, and controlling. The findings indicate that the management of market retribution in Bangkir Village has not been fully effective. Contributing factors include inconsistent trader data, underutilized market infrastructure, and a lack of socialization or outreach regarding retribution policies, all of which have led to low awareness and compliance among traders.